Web-Based Letter Filing System at the North Sumatra Provincial Representative Office of the Financial and Development Supervisory Agency - Andrea Lestari; Heri Kurniawan; Niko Surya Atmaja (Bahasa Indonesia, 2026)
Mail management is an important activity in various organizations, including government agencies, private companies, and educational institutions. With the advancement of technology, manual filing systems that use paper and filing cabinets are being phased out. The North Sumatra Provincial Representative Office of the Financial and Development Supervisory Agency (BPKP), as a state financial supervisory agency, receives a large volume of mail every day. The manual letter filing process often causes various problems, such as lost or damaged letters and overflowing filing cabinets. This can potentially cause delays in decision-making and increase the risk of losing important files. The emergence of the need for a more efficient filing system has encouraged the development of a website-based letter filing system. By implementing a good filing system, organizations can maintain information security, improve work efficiency, and support better decision-making. The method used is a descriptive method by collecting facts and information accurately at the research site. The research results successfully implemented a website-based letter filing system at the BPKP Representative Office of North Sumatra Province to overcome the obstacles that arose from the manual system. Overall, the implementation of this system helps maintain information confidentiality and supports a faster and better decision- making process for the organization.